Governance and Quintuple Helix innovation model: Insights from the local government of East Luwu Regency, Indonesia - Abdillah Abdillah; Abdillah Abdillah; Ida Widianingsih; Rd Ahmad Buchari; Nuryanti Mustari; Syafiuddin Saleh (Frontiers in Climate, 2022)
Climate change issues pose complex social and ecological challenges to rural communities in East Luwu Regency, Indonesia. This can be overcome through a collaborative, sustainable, and distributed innovation process for regional resilience and independence in each innovation sector. This study examines the concept of rural living as an inter-organizational interaction design and the process of developing sustainable rural innovation, where multi-stakeholder interaction forms the Quintuple Helix innovation model through a multidimensional case study design that focuses on the concept of innovation participation, knowledge production, innovation ecosystem as a social subsystem system, and socioecological transition toward developing independent rural areas, sustainability of rural innovation programs, and disaster preparedness in East Luwu Regency. This research method is qualitative-explorative with a case study approach exploring the social and ecological systems of rural communities in East Luwu Regency, Indonesia to provide a deeper understanding of the rural innovation process to address socio-ecological challenges through the importance of government-public-private-university synergy and its context in the Magani and Sorowako Villages, East Luwu Regency. The results of this study indicate that the strength of the innovation driver resulting from the cooperation between the East Luwu Government and PT Vale Tbk is the key to the sustainability of village innovations that encourage village innovation and village community participation in the village innovation process so that it has an impact on village community independence and environmental sustainability in East Luwu Regency. However, village innovation in East Luwu Regency still needs to be improved in terms of communication and coordination between actors and sectors.